2009
DOI: 10.1093/molbev/msp064
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Ascendancy of a Chimeric Fusion Gene: The  / -Globin Gene of Paenungulate Mammals

Abstract: The delta-globin gene (HBD) of eutherian mammals exhibits a propensity for recombinational exchange with the closely linked beta-globin gene (HBB) and has been independently converted by the HBB gene in multiple lineages. Here we report the presence of a chimeric beta/delta fusion gene in the African elephant (Loxodonta africana) that was created by unequal crossing-over between misaligned HBD and HBB paralogs. The recombinant chromosome that harbors the beta/delta fusion gene in elephants is structurally simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 49 publications
5
47
0
Order By: Relevance
“…We assumed that gene conversion affected only the selected loci (which were stand-ins for the two HBB paralogs) and that allelic and nonallelic gene conversion occur at equal rates. The former assumption is justifed by the well-documented pattern in the a-and b-globin gene families of mammals that nonallelic gene conversion is almost exclusively restricted to coding sequence (Storz et al 2007bHoffmann et al 2008a,b;Opazo et al 2008Opazo et al , 2009Runck et al 2009Runck et al , 2010. We also assume that the conversion tract spans the entire sequence of the recipient gene, which again is consistent with empirical data for mammalian b-globin genes (Borg et al 2009).…”
Section: Simulation Studysupporting
confidence: 87%
“…We assumed that gene conversion affected only the selected loci (which were stand-ins for the two HBB paralogs) and that allelic and nonallelic gene conversion occur at equal rates. The former assumption is justifed by the well-documented pattern in the a-and b-globin gene families of mammals that nonallelic gene conversion is almost exclusively restricted to coding sequence (Storz et al 2007bHoffmann et al 2008a,b;Opazo et al 2008Opazo et al , 2009Runck et al 2009Runck et al , 2010. We also assume that the conversion tract spans the entire sequence of the recipient gene, which again is consistent with empirical data for mammalian b-globin genes (Borg et al 2009).…”
Section: Simulation Studysupporting
confidence: 87%
“…The authors wish it to be known that, in their opinion, the first two authors should be regarded as joint First Authors. fused globins have been reported, occasionally supplanting the parental gene form, as was the case for the fusion of /Á globin, before the radiation of Paenungulata (the clade containing elephants, dugongs and manatees and hyraxes) (Opazo et al, 2009). Similarly, some of the toxins exploited by sea anemones to paralyse their preys have evolved by gene fusion, as they improved the transcript stability and secretion of these toxins (Moran et al, 2009).…”
Section: Biological and Evolutionary Motivation For Studying Gene Fusionmentioning
confidence: 99%
“…Multiple rounds of duplication and divergence have produced diverse repertoires of α- and β-like globin genes that are ontogenetically regulated such that functionally distinct Hb isoforms are expressed during different stages of prenatal development and postnatal life (Alev et al 2009; Brittain 2002; Hardison 2001; Hoffmann et al 2008a,b; Opazo et al 2008a,b, 2009; Storz et al 2011b). Surprisingly, however, phylogenetic analyses of the α- and β-globin gene families have revealed that genes with similar stage-specific expression patterns in different species do not necessarily represent 1:1 orthologs that were inherited from a common ancestor (Czelusniak et al 1982; Hoffmann et al 2010b; Opazo et al 2008a; Storz et al 2011a; Opazo et al 2012).…”
Section: Convergent Co-option Of Paralogous Genes For Similar Funcmentioning
confidence: 99%